2016
DOI: 10.1177/000313481608200320
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Previsit Education in Breast Cancer Patients: A Study of a Shared-decision-making Tool

Abstract: To enhance shared decision-making for patients with breast cancer, we developed an evidence-based educational breast cancer video (BCV) providing an overview of breast cancer biology, prognostic indicators, and surgical treatment options while introducing health care choice. By providing patients access to a BCV with information necessary to make informed surgical decisions before seeing a surgeon, we aimed to increase patient participation in the decision-making process, while decreasing distress. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that most breast cancer patients feel more informed than they actually are. 19,23,43 So, consistent with past research 18,19,23,[43][44][45] and the Institute of Medicine special report, 21 there appears to be a substantial deficiency in the informing of women about their breast cancer treatment options. Some patients (and therefore some doctors too) might feel that being "somewhat informed" is sufficient and satisfactory.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Previous studies have shown that most breast cancer patients feel more informed than they actually are. 19,23,43 So, consistent with past research 18,19,23,[43][44][45] and the Institute of Medicine special report, 21 there appears to be a substantial deficiency in the informing of women about their breast cancer treatment options. Some patients (and therefore some doctors too) might feel that being "somewhat informed" is sufficient and satisfactory.…”
mentioning
confidence: 75%
“…We also found that the vast majority of women were turning to other sources for information about treatment options (Table 2), consistent with past research. 19,44,45 Another large survey, conducted a decade ago with women in Los Angeles, CA and Detroit, MI, who had mostly undergone breast-conserving operations, also asked about what sources of information the women used. 19 Despite somewhat lower education levels, that survey's sample reported higher use rates of books (60%), scientific journal papers (52%), and magazines (51%) compared with our survey's lumpectomy-only patients' use of books or magazines (28%), and slightly lower rates of internet use (48% vs 58%), probably all due to the shift from print to digital during the past decade, and perhaps also due to culturally declining interest in reading.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While our approach incorporated a web-based educational tool that was reviewed after the initial consultation, an alternative or complementary approach is provision of education materials prior to the initial consultation with the aim of preparing the patient for discussion at the first visit. The feasibility of pre-visit educational videos in patients with breast cancer has been demonstrated elsewhere with favorable patient attitudes [23]. We are currently piloting the approach of a series of concise pre-visit videos in our clinic as an adjunct to the application.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of different genetic assays benefits diagnosis and prognostic prediction of BC. 18 HER2 gene encodes proteins, which are specifically coupled with ligands to form heterodimers, which cause conformational change of HER2 proteins, and autophosphorylation of tyrosine kinase inside the cytoplasm to activate signal pathways. The activity of this heterodimer is advantageous over heterodimers that are formed by other members in EGFR family, causing a cascade reaction.…”
Section: Discussionmentioning
confidence: 99%